Supportive effect of simultaneous immunization to other H-antigens on the female response to male-specific antigen in mice - Polácková, M; Viklický, V (Folia biologica, 1975)
The response of A-strain females to the male-specific antigen is very weak; both first- and second-set test skin grafts are rejected protractedly and about 50% of the grafts are retained in spite of generally present morphologic signs of cellylar immunity induced by these grafts. When the first-set skin graft involved H-incompatibilities additional to the MSA (such as H-2 only or H-2 plus multiple non-H-2) all the second-set grafts, which were only MSA-incompatible, underwent a markedly accelerated rejection. The possible mechanism of this adjuvant-like effect is discussed.
Keywords: Transplantation, Homologous; Immunization; Epitopes; Histocompatibility Antigens; Mice; zvířata; Immunity, Cellular; Graft vs Host Reaction; homologní transplantace; Skin Transplantation; transplantace kůže; epitopy; mužské pohlaví; reakce štěpu proti hostiteli; Sex Factors; buněčná imunita; imunizace; myši; ženské pohlaví; sexuální faktory; tvorba protilátek; Animals; Mice, Inbred C57BL; histokompatibilní antigeny; Antibody Formation; reakce antigenu s protilátkou; Antigen-Antibody Reactions; Male; myši inbrední C57BL; Female